Gene Segregation Effects on Fertility and Hatchability of Pure and Crossbred Chicken Genotypes in the Humid Tropics - Peters, S.O.; Ilori, B.M.; Ozoje, M.O.; Ikeobi, C.O.N.; Adebambo, O.A. (International Journal of Poultry Science, 2008)
This study was conducted to compare fertility and hatchability among pure and crossbred chicken genotypes. A total of three sires and thirty dams per genetic group were used in a study which was conducted over three months involving both direct and reciprocal crosses. A total number of 5804 eggs were set out of the total laid. Number of eggs fertile at first and second candling were significantly (P < 0.01) affected by both sire and dam strains. Similarly, number of eggs hatched, percentage fertility and hatchability were significantly (P < 0.01) affected by both sire and dam strains. There was also significant (P < 0.05) interaction effects between dam and sire strains on fertility and hatchability percentages. Matings involving pure strains of Naked Neck indigenous chicken resulted in lowest hatchability when compared to matings involving other pure and crossbred genotypes. Variations observed in percentage fertility and hatchability of eggs were attributed to segregation effects of genes in both pure and crossbred chicken genotypes used for the study.